Bridging Traditional Arabic Language Curriculum and Artificial Intelligence-Based Learning: An Analysis of Dar Al-Yusr Islamic Boarding School - Karsayuda, Rifa'iy; Ahmed Abdelrazek El Khatib,; Ahmad Tobroni, (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
The rapid advancement of Artificial Intelligence (AI) has transformed language education, creating opportunities to integrate technology with established curriculum models. This study analyzes the Arabic language curriculum implemented at Dar Al-Yusr Islamic Boarding School and examines its relevance to AI-based language learning. Employing a qualitative case study design, data were collected through curriculum document analysis, classroom observations, and semi-structured interviews with school leaders and Arabic language teachers. The data were analyzed using the interactive model of Miles, Huberman, and SaldaÃ±a and interpreted through the perspective of AI-supported language learning. The findings indicate that the curriculum is systematically organized around four interconnected components: learning objectives, curriculum content, instructional strategies, and assessment practices. The curriculum emphasizes linguistic competence as the foundation for understanding Islamic classical texts while integrating communicative skills through progressive learning stages. Furthermore, its structured competency progression, coherent curriculum architecture, and continuous assessment demonstrate strong pedagogical characteristics that align with adaptive and personalized AI-supported learning. The study concludes that traditional Arabic curricula can serve as a robust pedagogical foundation for AI integration, provided that digital literacy and AI-oriented instructional innovations are incorporated without compromising the educational values of Islamic boarding schools.